Pengembangan Media Augmented Reality (AR) Untuk Meningkatkan Pemahaman Siswa Pada Mata Pelajaran Geografi Kelas X SMA - Susanti, Widya; Rayendra; AmsalAmsal, Mutiara Felicita; Maiziani, Fitri (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Learning the material of volcanic eruption process in high school is still dominated by conventional media so that the visualization of abstract geological phenomena cannot be understood optimally by students. This study aims to develop and test the validity, practicality, and effectiveness of Augmented Reality (AR)-based learning media on the material of volcanic eruption process for grade X students at SMAN 5 Pariaman. The study used the Research and Development method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Product validation was carried out by media experts and material experts, while the field test involved 32 grade X students. The effectiveness of the media was tested using a one-group pretest-posttest design through N-Gain score analysis. The results showed that the media obtained a validity score from media experts of 4.53 and material experts of 4.72 with a very valid category. The results of the practicality test obtained an average score of 4.62 which is included in the very practical category. Meanwhile, the results of the effectiveness test showed an N-Gain value of 0.87 (87%) with a high category, which indicates an increase in student understanding after using the media. Thus, Augmented Reality-based learning media is suitable for use as a Geography learning medium because it is valid, practical, effective, and able to improve the quality of learning on the material on volcanic eruption processes.